Live Imaging of Innate and Adaptive Immune Responses in the Liver - Li, Lu; Zeng, Zhutian (Frontiers in Immunology, 2020)
Immune response in the liver is determined by the spatial organization and cellular dynamics of hepatic immune cells. The liver vasculature accommodates abundant tissue-resident innate immune cells, such as Kupffer cells, natural killer cells and natural killer T cells, to ensure efficient intravascular immunosurveillance. The fenestrated sinusoids also allow direct contact between circulating T cells and noncanonical antigen-presenting cells, such as hepatocytes, to instruct adaptive immune responses. Distinct cellular behaviors are exploited by liver immune cells to exert proper functions. Intravital imaging enables real-time visualization of individual immune cell in living animals, representing a powerful tool in dissecting the spatiotemporal features of intrahepatic immune cells during steady-state and liver diseases. This review summarizes current advances in liver immunology prompted by in vivo imaging, with a particular focus on liver-resident innate immune cells and hepatic T cells.